2017
DOI: 10.4049/jimmunol.1700142
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Critical Illness from Sepsis Is Associated with an Enhanced TCR Response

Abstract: Sepsis is characterized by a disproportionate host response to infection that often culminates in multiple organ failure. Current concepts invoke a deregulated immune reaction involving features of hyperinflammation, as well as protracted immune suppression. However, owing to the scarcity of human data, the precise origin of a long-term suppression of adaptive immunity remains doubtful. We report on an explorative clinical study of chronic critical illness (CCI) patients aimed at assessing the long-term conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 72 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…41 Besides the numerical loss or clonal shift, multiple dysfunctions in T cells' metabolism and activation in sepsis have been reported. 44 Nonetheless, the extent to which these cell-intrinsic impairments contribute to post-sepsis immunosuppression has now been challenged, 45,46 implying a prominent role of T cells' extrinsic cues in the post-sepsis environment (eg, defective antigen presentation). Also, the impact of sepsis on non-conventional, but biologically potent T-cell subsets such natural killer T cells or γδ T cells deserves more attention.…”
Section: Immunological Gaps During Sepsismentioning
confidence: 99%
“…41 Besides the numerical loss or clonal shift, multiple dysfunctions in T cells' metabolism and activation in sepsis have been reported. 44 Nonetheless, the extent to which these cell-intrinsic impairments contribute to post-sepsis immunosuppression has now been challenged, 45,46 implying a prominent role of T cells' extrinsic cues in the post-sepsis environment (eg, defective antigen presentation). Also, the impact of sepsis on non-conventional, but biologically potent T-cell subsets such natural killer T cells or γδ T cells deserves more attention.…”
Section: Immunological Gaps During Sepsismentioning
confidence: 99%
“…T cells were eluted into the cell culture medium (RPMI 1,640 medium supplemented with penicillin and streptomycin and 10% heat-inactivated fetal calf serum (FCS) and kept in a humidified atmosphere at 37 °C and 5% CO 2 for 24 h before stimulation. Peripheral T cells from a donor and patient blood were isolated and cultured in the same way out of PBMCs, except that a step of erythrocyte lysis was included before magnetic sorting 15 .…”
mentioning
confidence: 99%
“…The co-expression of a late activation marker in parallel with a characteristic phenotype of T-cell exhaustion suggests a potential role for T-cell activation in the development of T-cell alterations following septic shock. Similarly, it has been shown that T cells from patients with sepsis present an activated phenotype [46, 47]. Furthermore, this potential role for T-cell activation is supported by ex vivo data.…”
Section: Discussionmentioning
confidence: 70%